Influence of mexidol on early genomic response and morphofunctional parameters of the brain cortex sensorimotor zone neurons after arteria carotis communis occlusion - Chekman, I. S.; Belenichev, I. F.; Yakovleva, I. Yu.; Gorchakova, N. A.; Buchtiyarova, N. V.; Morguntsova, S. A.; Brazhko, O. O.; Levich, S. V.; Бєленічев, Ігор Федорович; Бухтіярова, Ніна Вікторівна; Моргунцова, Світлана Андріївна; Левіч, Сергій Вадимович (My University, 2015)
Objective: One of the most important problems of modern neuropharmacology is a development of new routes for pharmacological correction of cerebral strokes, as a reason of significant increase in morbidity, steady loss of working efficiency, and heavy mortality. Ischemic stroke is a multifactor pathological process and occurs primarily in the midst of a mismatch of blood supply level and metabolic brain tissue processes. Medications of secondary neuroprotection (antioxidants, metabotropic and nootropic drugs, and neuropeptides) take an important place in the treatment of ischemic stroke. Nowadays, the antioxidant mexidol (2-ethyl-6-methyl- 3-hydroxypyridine succinate) is widely used in clinical practice as a neuroprotector. However, its influence on morphofunctional state of neurons and genome response hadn’t been studied yet. The aim of the current study was to evaluate the neuroprotective activity of mexidol by its ability to influence the mode of immediate early response genes’ expression and morphofunctional neuron parameters. Materials and Methods: Research has been carried out on sufficient number of experimental rats. For morphological and histoimmunochemical study brain tissue of experimental animals was used. We studied: Cell composition in the area of IV-V cortex layers; density, area, and RNA concentration of normal, apoptotically, and destructively changed neurons. Results: Modeling of ischemic brain damage led to significant change in the genome response which was manifested by an impairment of a mode of expression of immediate early response gene c-fos. Administration of mexidol (250 mg/kg) caused neuroprotective effect. Conclusions: Intraperitoneal administration of mexidol for 21 days after arteria carotis communis occlusion increases c-fos gene expression, thus showing neuroprotective action of the drug.
Keywords: arteria carotis communis occlusion; c-fos gene expression; mexidol; neuroprotection